Inisiasi Pembentukan Agen “SARAS” (Sa Tra Miras) di Asrama Mahasiswa Mamberamo Raya - Violita, Fajrin (Jurnal SOLMA, 2025)
Background: The high rate of alcohol consumption among teenagers not only poses a risk for disease but also triggers deviant behaviors such as violence, traffic accidents, and risky sexual behavior. Alcohol consumption can also negatively affect the learning process due to decreased concentration. The purpose of this community service activity is to encourage the formation of “SARAS” (Sa Tra Miras) Agents who will act as continuous education providers and raise awareness about the negative impacts of alcoholic beverages in the Mamberamo Raya Student Dormitory. Methods: This community service was carried out in partnership with the Mamberamo Raya Student Dormitory management. The method was brainstorming, supported by poster media. A pre- and post-test questionnaire is used to assess the impact of the activity. Results: The initiation of "SARAS" (Sa Tra Miras) Agents involved 11 student participants. The program began with a presentation, followed by an interactive brainstorming discussion. Results from the pre- and post-tests indicated an increase in knowledge about alcohol, from 8.18 to 9.64. This community service activity has introduced the concept of peer educators and received a good response from the dormitory management. Conclusions: This service focuses on community-based interventions in the dormitory area and uses the slogan "SARAS" (Sa Tra Miras) which is appropriate to the local language. In the long term, there is a commitment to follow up on the official formation of the "SARAS" Agent.